Relative age effect in female sport: a diachronic examination of soccer players - Delorme, N.; Boiche, J.; Raspaud, M. (Scandinavian Journal of Medicine & Science in Sports, 2010)
he relative age effect (RAE) is a biased distribution of elite athletes' birthdates, with an overrepresentation of those born at the beginning of the competitive year and an underrepresentation of those born at the end. Despite an abundant literature, the impact of sex on this phenomenon remains neglected by most researchers. This study investigated the whole sample of female soccer players affiliated to the French Soccer Federation for the 2006-2007 season (n=57 892). It first aimed at testing the presence of RAE depending on age. Next, we looked at the birthdates of dropout players during the next season (n=15 285), to test whether relative age accounts for dropout from the activity. The analyses revealed significant differences between the expected and the observed distributions for all age categories. Furthermore, a significantly biased distribution of dropout players' birthdates was found for the <10, <14, and <17 categories. On the whole, dropout players are underrepresented in Q1 and Q2, but overrepresented in Q3 and Q4. This study completes the literature on RAE among females, but the inconsistency of the results calls for more research on this population.